Low-dose ionizing radiation and cancer mortality among enlisted men stationed on nuclear-powered submarines in the United States Navy. (3rd October 2022) - Friedman-Jimenez, George; Kato, Ikuko; Factor-Litvak, Pam; Shore, Roy
Abstract: Background: Men stationed on nuclear-powered submarines are occupationally exposed to external ionizing radiation at very low levels and radiation dose for each individual is closely monitored. Little is known about ionizing radiation (IR) risks of cancer mortality for populations with levels of cumulative ionizing radiation exposure this low. Materials and methods: This historical cohort study followed 85, 033 enlisted men who had served on a nuclear-powered submarine in the U.S. Navy between 1969 and 1982 to determine patterns of cancer mortality. Occupational radiation doses were measured by badge dosimeters for each individual for all periods of Navy service potentially involving radiation exposure. Deaths were ascertained through 1995 by searches of multiple national mortality databases. Within-cohort dose-response relationships for cancer mortality were estimated using linear Poisson regression models. Individual-level smoking status was not available so cancer risks were estimated separately for cancers with and without previously published evidence of consistently moderate or strong associations with smoking. Results: A total of 584 cancer deaths occurred during a follow-up period of up to 27 years. The mean and median cumulative occupational radiation doses received while in the Navy were 5.7 and 1.1 milliSieverts (mSv), respectively, range 0–242 mSv. Mortality Excess Relative Risks (ERRs) per 10 mSv and 95% confidence intervals (CI) were 0.053 (CI −0.03, 0.17) for all cancers, 0.052 (CI −0.03, 0.18) for all solid cancers, and 0.003 (CI −0.29, 0.30) for leukemias excluding chronic lymphocytic leukemia. The ERRs per 10 mSv were 0.052 (CI −0.07, 0.17) for cancers previously associated with smoking and 0.012 (CI −0.10, 0.12) for cancers that were not. Conclusions: The ERR point estimates for solid cancers and leukemia were statistically compatible with those reported in previously published studies of other ionizing radiation-exposed and monitored cohorts, albeit with wide confidence intervals. This study, with high-quality measurements of in-Navy occupational external IR doses, high follow-up proportion, and detailed IR dose-response analyses, is consistent with the premise of small excess cancer risks from low-dose IR.